The Italian "Reddito di Cittadinanza" one year later - Fausto Favero (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
The present paper discusses the elements and workings of the so called "Reddito di Cittadinanza" (translatable as "Citizenship Income"), the scheme for minimum income protection that was recently adopted by the Italian government and that undoubtedly represents a turning point for the country's policy against poverty. In order to provide an evaluation of its effectiveness with respect to its declared ambitions, the analysis will be based both on the scheme's theoretical design, the degree of consistency with the surrounding institutional context and the interpretation of the most recent statistic reports. The paper is divided in three parts. The aim of the first section is to provide an organic background to the policy in discussion: a theoretical clarification over the different types of minimum income protection schemes is provided, followed by a historical-institutionalist review of such policies across Europe since the end of World War II. I will also examine the most relevant details of the picture of the Italian institutional setting for social assistance. The understanding of the critical imbalances in the welfare structure is a necessary and crucial phase of the development of an effective policy against systemic problems such as poverty and unemployment and will therefore be a fundamental element supporting this paper's conclusions. The second section will depict the structure and the functioning of the policy itself, with an explanation of the political developments and debate that led to its adoption and that shaped some of its characteristics. Finally, the third and concluding part of the research discusses the most important discrepancies and shortcomings of the policy, based on the previous findings and the study of the connecting link between poverty and unemployment, a relationship that, as it will be argued, the legislator failed to grasp.
Keywords: 330; Minimum Income Scheme; Italy; Welfare-state; Populism; Poverty; Unemployment; Social Inclusion; Basic Income